2008
DOI: 10.1111/j.1442-200x.2008.02538.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic deletions in thedystrophingene in 211 Pakistani Duchenne muscular dystrophy patients

Abstract: The observed proportion of intragenic deletions in the Pakistani population is relatively low, which is comparable with most of the Asian data. Also, deletions in 67 patients (77.9%) are in agreement with the frame-shift rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
8
19
0
Order By: Relevance
“…The frequency of deletion was more common than duplications, similar to frequency reported from other parts of India [2327]. The reported deletion rates in Pakistanis is 40.7%, Chinese 66.25%, Korean 45.5% and in Taiwanese patients 36%, thus showing possible variations among different populations [22, 2830]. The duplication rate in our cases mainly involved larger fragments and the pattern of duplication was more towards the distal part of the gene unlike other populations [22].…”
Section: Discussionsupporting
confidence: 78%
“…The frequency of deletion was more common than duplications, similar to frequency reported from other parts of India [2327]. The reported deletion rates in Pakistanis is 40.7%, Chinese 66.25%, Korean 45.5% and in Taiwanese patients 36%, thus showing possible variations among different populations [22, 2830]. The duplication rate in our cases mainly involved larger fragments and the pattern of duplication was more towards the distal part of the gene unlike other populations [22].…”
Section: Discussionsupporting
confidence: 78%
“…Presently, deletions almost involved hot spots residing on the mid-distal exons of dystrophin gene (exons 45-50) as previously reported in various studies [10][11][12]. Exons 50 was the most frequently deleted exon which is in the line with previous report of Pakistani population analyzed by M-PCR alone [13]. The least frequent deletions were attributed to proximal (5 0 ) and distal (3 0 ) exons.…”
Section: Novel Mutation Identified By Sequencingsupporting
confidence: 80%
“…Using M-PCR, we could detect all of the deletions including large ones similar to other studies on Taiwanese and Pakistani patients [24]. However, inability to detect intragenic gene rearrangements especially large deletions or duplications has been described as one of the major drawbacks of M-PCR [13]. MLPA or quantitative PCR are alternative methods to characterize the female carriers and duplications [21].…”
Section: Novel Mutation Identified By Sequencingmentioning
confidence: 77%
See 1 more Smart Citation
“…[32] The deletion rate in our study was about 73% and was similar to the frequency reported from the other parts of India. [33] The reported frequency of dystrophin gene deletions in other countries in Asia is quite variable: 40.7% in Pakistan, [34] and 66.25% in China. [35] In Egypt, an African country, it was 61.1%.…”
Section: Carrier Testingmentioning
confidence: 97%